The Shackles of The Mirror? - A Case Study on Body Dysmorphic Disorder - Smita B.Thomas,; Suphala Kotian, (International Journal of Management, Technology and Social Sciences (IJMTS), 2021)
Purpose: This case study was done to do a detailed study on the recent trends with photographs and how it affects the body dysmorphic disorder [BDD] across all genders and age groups. The intention was to understand how is body dysmorphic disorder affects persons eating habits, social interaction, and body image. In this article, various research studies and scholarly articles were studied to understand in detail regarding Body dysmorphic disorder. The emphasis was given on age, gender, social media networking site users, etc. It was also intended to study how the media influences people towards a certain skin color and body type. It was found not a single study was done in India though there are articles by Indian authors on body shaming, body image, and how media is obsessed with unrealistic beauty standards which indirectly creates body image concerns in people. This case study justifies the need for studies to be done in India to identify Body dysmorphic disorder using various scales like Body image concern inventory, etc. Objective: This case study was done to understand the studies done on body dysmorphic disorder around the world. To understand the pattern, occurrence ratio between youngsters and elderly and social media users and non-users. Design/Methodology/Approach: Detailed Review of literature was done on various scholarly articles provided over medical, psychology, and journal websites. Findings/Results: Most of the studies were done in European countries and very few in Asia. The studies revealed that women are more affected by BDD than men. People active on social networking sites, following celebrities, and media were more discontent with their body parts or in general. Studies also show that the younger population is more affected by body dysmorphic disorder. It was also noted that there was no direct study done in India for identifying body dysmorphic disorder. Type of Paper: Research Case Study.